2020
DOI: 10.1136/bcr-2019-233117
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3D modelling and 3D printing for the diagnostic process, decision making and preoperative planning of periprosthetic acetabular fractures

Abstract: Periprosthetic acetabular fractures represent an uncommon but challenging complication of total hip arthroplasty (THA), mostly related to low-energy trauma and pathological conditions that reduce bone quality. Therefore, particularly in elderly patients, these fractures are associated with periprosthetic osteolysis and bone loss. CT scan is considered the gold standard to define the fracture pattern; however, the presence of the prosthetic implants in situ limits the full view of the articular surface and bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Afterward, they transmitted all the analysis to an actual printed model of the whole pelvis and a particular fracture of the wall made from plastic to perform preoperative templating and planning for surgery. They conclude this technique would be useful, especially in patients with poor bone quality, 168 to facilitate surgery. 169 Another study was a challenging case of a 21 year old man diagnosed with osteosarcoma.…”
Section: Toward Personalized Medicine Frommentioning
confidence: 99%
“…Afterward, they transmitted all the analysis to an actual printed model of the whole pelvis and a particular fracture of the wall made from plastic to perform preoperative templating and planning for surgery. They conclude this technique would be useful, especially in patients with poor bone quality, 168 to facilitate surgery. 169 Another study was a challenging case of a 21 year old man diagnosed with osteosarcoma.…”
Section: Toward Personalized Medicine Frommentioning
confidence: 99%
“…Another issue with conventional imaging and planning during revision are the artefacts in CT scans, caused by implants in situ. In such scenarios, especially for periprosthetic fractures, Marongiu et al have shown that a 3DP model aids in preoperative templating and sizing [42]. It includes measures of shape, location and extent of distorted anatomy including bone loss.…”
Section: Pre-operative Planning and Decision-makingmentioning
confidence: 99%
“…Biomechanical models allow evaluating and predicting the behavior of potential fixation configurations in different types of fractures using computer simulation and laboratory tests [8]. Computational models also aid in making several therapeutic decisions, such as patient positioning for radiotherapy treatments [9], kidney stones surgery [10], and preoperative orthopedic planning processes [11], [12]. The construction of biomechanical models starts with the acquisition of a stack of 2D cross-sectional medical images (i.e., computerized tomography, CT), which are then volumetrically represented and used in numerical computational analyses.…”
Section: Introductionmentioning
confidence: 99%